The Effect of Endorphin Massage to Reduce Back Pain in Third Trimester Pregnant Women - Zelharsandy, Vika Tri; Soleha, Marchatus; Anggeriani, Rini (GLOBAL HEALTH SCIENCE GROUP, 2024)
Labor pain is a physiological condition and is something that is usually felt by pregnant women in the third trimester. However, if it is not treated with proper pain management, it will cause other problems, including anxiety, stress/depression, muscle tension and feelings of worry. Labor pain can be reduced by using the Endorphin Massage technique, where this technique is therapy or massage carried out through the surface of the skin so that it can increase the feeling of comfort and can result in a block against painful stimuli. The aim of this research is to determine the effectiveness of endorphin massage to reduce back pain in third trimester pregnant women. This type of research uses a quasi-experimental design whose design uses one group pretest-posttest. The number of samples in this study was 15 third trimester pregnant women with back pain. Data analysis was carried out using univariate and bivariate methods using non-parametric tests with the Wilcoxon test, because the Wilcoxon test is used as an alternative to the paired sample t test if the research data is not normally distributed. The results of this study show a significant value of 0.00, which means that the value of 0.00 is less than 0.05, indicating that there is a difference before and after the endorphine massage technique is given.